2012
DOI: 10.1097/pas.0b013e31824104c5
|View full text |Cite
|
Sign up to set email alerts
|

Perineural and Intraneural Invasion in Posttherapy Pancreaticoduodenectomy Specimens Predicts Poor Prognosis in Patients With Pancreatic Ductal Adenocarcinoma

Abstract: Perineural invasion (PNI) is one of the established prognostic factors in pancreatic ductal adenocarcinoma (PDAC). However, the prognostic significance of PNI in patients with PDAC who received neoadjuvant therapy and pancreaticoduodenectomy (PD) is not clear. In this study, we performed detailed examination of neural invasion in PD specimens from 212 patients with PDAC who received neoadjuvant chemoradiation (treated group) and 60 untreated patients at our institution between January 1999 and December 2007. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 21 publications
11
114
0
1
Order By: Relevance
“…The innermost layer of the nerve is the endoneurium. The invasion of cancer cells in the endoneurium, named intraneural invasion, is associated with a worse prognosis than the invasion around or in the other layer of the nerves [18, 19]. A variety of cells from the nerve can facilitate cancer progression.…”
Section: – Nerves and Schwann Cells Form A Unique Tumor Microenviromentioning
confidence: 99%
“…The innermost layer of the nerve is the endoneurium. The invasion of cancer cells in the endoneurium, named intraneural invasion, is associated with a worse prognosis than the invasion around or in the other layer of the nerves [18, 19]. A variety of cells from the nerve can facilitate cancer progression.…”
Section: – Nerves and Schwann Cells Form A Unique Tumor Microenviromentioning
confidence: 99%
“…Most patients are in an advanced or metastatic condition at the time of diagnosis, which results in a poor prognosis (Chatterjee et al, 2012;Li et al, 2004). Recurrence remains the main cause of cancer-related death after curative resection in a substantial proportion of patients with PDAC (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…14 of the remaining 35 studies (Kim et al, 2006;Murakami et al, 2008;Balentine et al, 2010;Chu et al, 2010;Kanda et al, 2010;de Jong et al, 2011;Jamieson et al, 2011;Kneuertz et al, 2011;Maithel et al, 2011;Singal et al, 2011;Chatterjee et al, 2012;Watanabe et al, 2012;Xie et al, 2012;Fisher et al, 2013) were excluded because they were reported by the same institutions as other studies. 21 studies (Ozaki et al, 1999;Mitsunaga et al, 2005;Nakagohri et al, 2006;Pawlik et al, 2007;Kazanjian et al, 2008;Kato et al, 2009;Nagai et al, 2009;Sergeant et al, 2009;Ben et al, 2010;Murakami et al, 2010;Bachellier et al, 2011;Kim et al, 2011;Schiffman et al, 2011;Cheng et al, 2012;Jamieson et al, 2012;Lee et al, 2012;Murata et al, 2012;Sahin et al, 2012;Takahashi et al, 2012;Turrini et al, 2013;Xie et al, 2013) were included in the final meta-analysis, comprising one case matched controlled study and 20 retrospective cohort studies (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%